Yield potential and economic analysis of traditional waterlogged agroforestry systems in North-East (Tripura), India - Sarkar, Pradip Kumar; Sarkar, Pranati; Pala, Nazir A. (Indian Journal of Agroforestry, 2019)
In present investigation, an attempt was made to estimate yield under different fertilizer doses and economic analysis of waterlogged traditional agroforestry system (locally known as Doba) in Tripura, India. The experiment was carriedout using randomized block design. Seven treatments consisting of different fertilizer doses, following four replications were applied during 2013-16 to evaluate the effect on yield of Colocasia. Among all the treatments, T [N P K ; application of urea 5 57 57 37 @ 74.56 kg ha-1, SSP @ 186.39 kg ha-1 and MOP @ 62.13 kg ha-1 after 15 days of transplanting and application of DAP @124.26 kg ha-1 before one month of harvesting during growth stage] was found better than other treatments. In T , higher corm 5 length (74.24 cm), corm diameter (12.10 cm), corm volume (12554.75 cm3), corm yield (5.07 kg plant-1), yield of stolon (1.36 kg plant-1), average length of petioles (123.25 cm), number of petioles (8) and higher yield of petioles (1.18 kg plant-1) wereobserved. Impact of different treatments with respect to corm length, corm volume and corm yield plant-1 were in the order of T >T >T >T >T >T >T . The study revealed that this agroforestry model (average B: C ratio = 6.35) can be promoted as one of 5 6 4 7 2 3 1 the important means for livelihood of farming communities in waterlogged areas in Tripura and other parts of North-East India.